2019
DOI: 10.1021/acs.inorgchem.8b03081
|View full text |Cite
|
Sign up to set email alerts
|

Rhombohedral Potassium–Zinc Hexacyanoferrate as a Cathode Material for Nonaqueous Potassium-Ion Batteries

Abstract: Rhombohedral potassium–zinc hexacyanoferrate K1.88Zn2.88[Fe­(CN)6]2(H2O)5 (KZnHCF) synthesized using a precipitation method is demonstrated as a high-voltage cathode material for potassium-ion batteries (PIBs), exhibiting an initial discharge capacity of 55.6 mAh g–1 with a discharge voltage of 3.9 V versus K/K+ and a capacity retention of ∼95% after 100 cycles in a nonaqueous electrolyte. All K ions are extracted from the structure upon the initial charge process. However, only 1.61 out of 1.88 K ions per for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 63 publications
1
26
0
1
Order By: Relevance
“…Thus, this lower cost current collector can be used both as anode and cathode . Considering that copper prices are more volatile in the market than aluminum, this relevant aspect may represent a competitive aspect driving down costs in large scale applications …”
Section: Energy Storage Applicationsmentioning
confidence: 99%
“…Thus, this lower cost current collector can be used both as anode and cathode . Considering that copper prices are more volatile in the market than aluminum, this relevant aspect may represent a competitive aspect driving down costs in large scale applications …”
Section: Energy Storage Applicationsmentioning
confidence: 99%
“…On the other hand, Zn-based PBA could usually present a higher discharge voltage (not lower than 3.9 V) than that of K/K ? in a non-aqueous electrolyte [81,82]. Although Zn-based PBA shows two pairs of redox peaks, only the C-coordinated Fe is electrochemically active [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…in a non-aqueous electrolyte [81,82]. Although Zn-based PBA shows two pairs of redox peaks, only the C-coordinated Fe is electrochemically active [81][82][83]. The detailed intercalation mechanism is not understood clearly for the two redox couples with only one redox center.…”
Section: Discussionmentioning
confidence: 99%
“…It displayed a super long‐term lifetime of over 8000 cycles at 200 mA g −1 [125] . Additionally, cube‐shaped K 1.88 Zn 2.88 [Fe(CN) 6 ] 2 ⋅ 5 H 2 O was also demonstrated as a high‐voltage (3.9 V vs. K/K + ) cathode material for PIBs [126] . The groups of Solanki [127] and Fu [128] also found that Prussian green (Fe III Fe III (CN) 6 ) had outstanding K + ‐storage capabilities as a cathode material for PIBs.…”
Section: Cathode Materialsmentioning
confidence: 98%